Représenter dieux et hommes dans le Proche-Orient ancien et dans la Bible: actes du colloque organisé par le Collège de France, Paris, les 5 et 6 mai 2015 - Römer, Thomas; Gonzalez, Hervé; Martin, Lionel-Édouard (Orbis biblicus et orientalis, 2019)
What was the function of representing deities and also humans in the ancient Near-East? Which were the different ways of making gods visible, and the specific functions of these representations? Might these material and visual representations help us to better understand official cults, as well as private cults? What was the role of images in the royal cult? Was the king the only “image” of the gods, or could all humans fulfill this role? Why were cult images forbidden? Does the biblical prohibition have any precedent or parallel in the ancient Near-East, or elsewhere? And how do the ways of representing gods and humans change in the absence of cultic images? The conference Representing Gods and Humans in the Ancient Near-East and in the Bible, held at the Collège de France, Paris, on May 5-6 2015, sought to shed light on these questions surrounding the image, a critical issue for our understanding of ancient as well as modern religions